1979
DOI: 10.1021/bi00573a011
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of previtamin D3 from the skin of rats exposed to ultraviolet irradiation

Abstract: The process of the photolytic activation of vitamin D precursor(s) in the skin has been elucidated by a detailed analysis of the products formed after ultraviolet light exposure. The photolytic product isolated from the skin of rats exposed to ultraviolet irradiation was identified as previtamin D3 by several criteria including its (a) characteristic ultraviolet absorption spectrum, (b) mass spectrum, and (c) thermal isomerization to vitamin D3, which itself was identified also by mass spectroscopy. Vitamin D3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…Our data lend support to the hypothesis that plasma 25-OHvitD can be used as a surrogate marker for UV-B radiation from sun exposure and hence be used to identify persons at risk of acquiring skin cancer. Biologically, this is supported by previous studies that have shown that UV radiation induces both DNA damage and vitamin D synthesis (Holick et al, 1977(Holick et al, , 1979Adams et al, 1982;MacLaughlin et al, 1982;Freeman et al, 1989), that vitamin D formation in the skin increases with increasing UV-B radiation exposure (Adams et al, 1982;MacLaughlin et al, 1982), and that in areas with high UV index the incidence of non-melanoma skin cancer and, to a lesser degree, melanoma is increased in Caucasians (Armstrong and Kricker, 2001), as are plasma 25-OH-vitD levels (McCullough et al, 2010).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Our data lend support to the hypothesis that plasma 25-OHvitD can be used as a surrogate marker for UV-B radiation from sun exposure and hence be used to identify persons at risk of acquiring skin cancer. Biologically, this is supported by previous studies that have shown that UV radiation induces both DNA damage and vitamin D synthesis (Holick et al, 1977(Holick et al, , 1979Adams et al, 1982;MacLaughlin et al, 1982;Freeman et al, 1989), that vitamin D formation in the skin increases with increasing UV-B radiation exposure (Adams et al, 1982;MacLaughlin et al, 1982), and that in areas with high UV index the incidence of non-melanoma skin cancer and, to a lesser degree, melanoma is increased in Caucasians (Armstrong and Kricker, 2001), as are plasma 25-OH-vitD levels (McCullough et al, 2010).…”
Section: Discussionmentioning
confidence: 53%
“…However, the wavelength of UV radiation that causes DNA damage in skin cells also induces vitamin D production in keratinocytes (Holick et al, 1977(Holick et al, , 1979Adams et al, 1982;MacLaughlin et al, 1982;Freeman et al, 1989), which promotes differentiation and reduces proliferation in normal skin cells and skin cancer cell lines (Colston et al, 1981;Eisman et al, 1987;Evans et al, 1996;Bikle, 2004;Tang et al, 2011b). Furthermore, vitamin D receptor knockout mice have increased susceptibility toward UV radiation-induced skin tumors (Zinser et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Crystalline vitamin D 2 (ergocalciferol), ergosterol and vitamin D 3 (cholecalciferol) standards were obtained from Sigma-Aldrich Co. (St. Louis, MO, USA). Crystalline previtamin D 2 , tachysterol 2 and lumisterol 2 were prepared and purified by UV irradiation of ergosterol based on previously published methods (Holick et al, 1979). All other chemicals and solvents used were of analytical or HPLC grade.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the in vivo-generated pre-D3 and vitamin D3 themselves in the irradiated rat skin were identified by GC-MS in the fourth report (4). On the other hand, HOLICK et al (5,6) identified the in vivo-generated pre-D3 in UV -irradiated rat skin by using HPLC and mass spectrometry, while in vitro-generated vitamin D3 in skin was also identified by EsVELT et al (7). Our results agreed in that the endogenous 7-DHC in the rat skin was photochemically converted to vitamin D3 via pre-D3 in the same manner as in a test tube by UV irradiation, then the generated vitamin could be metabolized normally to show the physiological effects.…”
Section: Discussionmentioning
confidence: 99%